Interdiscourse as Inherent Characteristic of Institutional Discourse (on the Example of Educational Discourse) - A. A. Gabets (Вестник Самарского университета: История, педагогика, филология, 2021)
The article is devoted to the types of interaction of educational discourse with other types of institutional communication: political, economic and medical. The author studies how fragments of discourse function and form semantic potential in official styles of speech where interdiscourse is traditional and describes forms of discourse genre interference caused by global events of 2020: coronavirus epidemic, presidential election in the USA and others. In the article educational discourse is understood in its broad sense which allows to examine the periphery of discourse practice where communication of individuals of equal status and variety of functional styles are natural. The process of interference is studied on micro and meso levels of discourse where certain lexico-sematic fields, key-words, clichs which characterize professional genres of communication serve as markers of interdiscourse and on macro level where historical and social context is considered to define functional styles. Methods of descriptive, discourse and contextual analyses are implemented. The author draws the conclusion that on all levels of institutional interaction the elements of educational discourse are semiotic components of communication, can serve as means of representation of political, economic or medical discourse practice, have pragmatic potential and can be used in argumentative or informative speech strategies the choice of which depends on the type of discourse. On macro level elements of educational discourse often extend beyond specific concepts limited to professional subjects and the discourse itself becomes a part of a bigger subordinating discourse formation.